Klondiker washing clothes with bucket and washboard in front of tent, Dawson, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Girl wanted" Original image in Hegg Album 24, page 31. Klondike Gold Rush.